2016
DOI: 10.3109/10641963.2016.1151527
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and pharmacological evaluation of 5-oxo-1,2,4-oxadiazole derivatives as AT1 antagonists with antihypertension activities

Abstract: A series of new 5-oxo-1,2,4-oxadiazole derivatives with 1, 4-disubsituted or 1, 5-disubsituted indole group was designed, synthesized, and pharmacologically evaluated. These derivatives displayed high affinities to the AT1 receptor at the same order of magnitude to losartan. The methyl ester with 1, 4-disubsituted indole group, 1 (5.01 ± 1.67 nM) showed high antihypertension activity on spontaneously hypertensive rats (SHRs). Its maximal response lowered 30 mmHg of mean blood pressure (MBP) at 10 mg/kg after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The acute toxicity of compound F5-2b was determined by LD 50 as 1551.71 mg/kg. Other indole derivatives have been prepared by the same group and studied as angiotensin II receptor 1 antagonists [ 167 , 168 , 169 , 170 ]. The examples given in Figure 5 show that a common feature of these compounds is the presence of an ortho -substituted phenyl ring with a carboxylic acid F5-3 [ 167 , 168 , 170 ] or 1,2,4-oxadiazole F5-4 [ 169 ] scaffold at position 1 of the indole unit.…”
Section: N -Arylated Indoles As Biologically Active Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute toxicity of compound F5-2b was determined by LD 50 as 1551.71 mg/kg. Other indole derivatives have been prepared by the same group and studied as angiotensin II receptor 1 antagonists [ 167 , 168 , 169 , 170 ]. The examples given in Figure 5 show that a common feature of these compounds is the presence of an ortho -substituted phenyl ring with a carboxylic acid F5-3 [ 167 , 168 , 170 ] or 1,2,4-oxadiazole F5-4 [ 169 ] scaffold at position 1 of the indole unit.…”
Section: N -Arylated Indoles As Biologically Active Substancesmentioning
confidence: 99%
“…Other indole derivatives have been prepared by the same group and studied as angiotensin II receptor 1 antagonists [ 167 , 168 , 169 , 170 ]. The examples given in Figure 5 show that a common feature of these compounds is the presence of an ortho -substituted phenyl ring with a carboxylic acid F5-3 [ 167 , 168 , 170 ] or 1,2,4-oxadiazole F5-4 [ 169 ] scaffold at position 1 of the indole unit. Similarly, the introduction of phenyl substituents was accomplished via nucleophilic aromatic substitution in refluxing DMF.…”
Section: N -Arylated Indoles As Biologically Active Substancesmentioning
confidence: 99%
“…After extraction and column chromatographic purification, 1,2,4-oxadiazole-5-one derivatives were obtained in 88 % yield. [18] As is known, tamoxifen used in the treatment of breast cancer has E and Z isomers, and there is a difference in effect between these isomers as an agonist/antagonist. Since this difference in effect is an undesirable in the therapeutic use of the drug, researchers are working to prevent rotation in the double bond in the triphenylethylene ring in order to prevent this.…”
Section: General Synthetic Methods Of 124-oxadiazolesmentioning
confidence: 99%
“…The SAR analysis of certain oxadiazole derivatives showed that compounds 43 and 44 are the top contenders as (FLAP) inhibitors with enhanced pharmacokinetic and pharmacodynamic properties. [86] Compounds 45 are diltiazem-like P-glycoprotein inhibitors that have recently been proposed as drug resistance inhibitors by blocking ABC efflux pumps. [86] As inhibitors of human mast cell tryptase, selective α-keto-1,2,4oxadiazoles 46 were designed, an enzyme linked to treat the acute and long-term symptoms of asthma.…”
Section: Antidiabetic Agentsmentioning
confidence: 99%